Doctors' Choice of Rehabilitation Measures for Patients Who Have Suffered Covid-19 - K. S. Lomonosov (Эпидемиология и вакцинопрофилактика)
Relevance. According to WHO, the number of patients with a new coronavirus infection amounted to more than 676 million people for the period from January 2020 to January 2023. It is obvious that the consequences of COVID-19 will prevail in medical practice in the coming years, so medical rehabilitation should be the focus of attention when providing medical care to patients with coronavirus infection.Aims. To investigate the approach to physicians' selection of rehabilitation interventions for patients who have undergone Covid-19.Materials and methods. The analysis of 1832 case histories of patients of one of the temporary covid hospitals in Moscow, who are being treated in the hospital in 2020–2022, was carried out. Statistical analysis was carried out using the StatTech v. 3.1.3 program (developed by Stattech LLC, Russia). Predictive models characterizing adherence to rehabilitation measures were developed using the logistic regression method.Results and discussions. The analysis of predictors of statistically significant regression models showed that when deciding on the appointment of rehabilitation measures or additional consultation when a patient is discharged from the hospital, doctors rely on pathologies already present in patients before COVID-19 disease, without taking into account the occurrence of possible pathology after a new coronavirus infection in any organ system. For example, the appointment of a cardiologist's consultation increases 6 times in the presence of a history of cardiovascular diseases or atherosclerosis and 10 times in the presence of cardiovascular diseases and atherosclerosis at the same time. The presence of bronchial asthma increased the probability of consulting a pulmonologist by almost 3 times, and in the absence of diabetes mellitus, the probability of getting additional advice from an endocrinologist decreased by 11 times.Conclusions. An individual rehabilitation plan should take into account the severity of the COVID-19 disease, the degree of damage to the lung tissue, heart, blood vessels and other organs. The regression models can be used for economic analysis in order to identify the need for working hours and the number of medical workers necessary to ensure the optimal volume and effectiveness of rehabilitation measures for patients who have suffered a new coronavirus infection.